2003
DOI: 10.1097/01.inf.0000048907.22286.b5
|View full text |Cite
|
Sign up to set email alerts
|

Community outbreak of perianal group A streptococcal infection in Denmark

Abstract: A clone of T type 28 seemed to be the cause of the largest cluster of PASI cases described thus far. Clarithromycin was effective as second line treatment. An estimated annual baseline incidence of 2 to 7 per 1000 in the local population indicates that PASI may not be as rare as previously estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Study of the prevalence of healthy S. pyogenes carriers and the molecular epidemiology of the isolates may provide useful information about the origin and spread of this infectious agent, allowing for more effective control measures. Pulsed-field gel electrophoresis (PFGE) (3,4,14) has been used as a standard technique for surveying epidemiology of S. pyogenes infections. Although arbitrarily primed PCR (AP-PCR)-based fingerprinting performed with the M13 primer has been widely used for molecular epidemiology of gram-negative (1, 2, 10) and gram-positive bacteria (11), there had been no study about its efficiency in typing S. pyogenes strains.…”
mentioning
confidence: 99%
“…Study of the prevalence of healthy S. pyogenes carriers and the molecular epidemiology of the isolates may provide useful information about the origin and spread of this infectious agent, allowing for more effective control measures. Pulsed-field gel electrophoresis (PFGE) (3,4,14) has been used as a standard technique for surveying epidemiology of S. pyogenes infections. Although arbitrarily primed PCR (AP-PCR)-based fingerprinting performed with the M13 primer has been widely used for molecular epidemiology of gram-negative (1, 2, 10) and gram-positive bacteria (11), there had been no study about its efficiency in typing S. pyogenes strains.…”
mentioning
confidence: 99%
“…The clinical and reference strains were analyzed by pulsed-field gel electrophoresis (PFGE) as described elsewhere (15) with supplementation of the lysis buffer with 22 l of mutanolysin (Sigma, St. Louis, Mo.) per ml (14). Calculation of similarity between PFGE patterns with the Dice coefficient and clustering by the unweighted pair group method using mathematical averages (UPGMA) was done in BioNummerics (Applied Maths, Kortrijk, Belgium) after the image was captured by Chemi Doc (Bio-Rad Laboratories).…”
mentioning
confidence: 99%
“…Regarding streptococcus at other sites, a recent case report documented perianal streptococcal dermatitis as the precipitating factor to a PANS initial episode and/or exacerbation in three children [35]. Interestingly, two of these children had a history of pharyngeal streptococcal infections, and research has suggested that pharyngeal strains of GAS can migrate to other areas of the body [36,37].…”
Section: Infectious Triggersmentioning
confidence: 95%